Simulation and experimental study of refuse-derived fuel gasification in an updraft gasifier - Thanh Xuan Nguyen-Thi; Thi Minh Tu Bui; Van Ga Bui (International Journal of Renewable Energy Development, 2023)
Refuse-derived fuel (RDF) made from the mixture of wood and loose rice husk increases the porosity of the fuel in the furnace to facilitate the gasification process. Simulation results show that CO is concentrated in the incomplete combustion zone and CO2 forms mainly in the fully burned area; CH4 forms in the reduction region, while H2 forms in the region of high temperature of the furnace. When the mixture composition was f=0.3, the CO concentration in the syngas reached about 21%, the H2 concentration reached about 2% and the CH4 concentration was too low to be ignored. When the mixture composition increased to f = 0.5, the CO concentration reached about 26%, the H2 concentration remained almost unchanged and the CH4 content increased to 6%. The calorific value of the syngas reached a maximum when f = 0.5 and the temperature of the reduction zone is in the range of 900K to 1200K. Air humidity affects CO concentration but not much on CH4 and H2 concentration as well as the syngas calorific value. The difference between simulation and experimental results is not more than 10% for CH4 concentration and not more than 14% for CO2 concentration. The power of the spark ignition engine is reduced by 30% when running on syngas compared to when running on gasoline.